2020
DOI: 10.1108/sajbs-10-2019-0172
|View full text |Cite
|
Sign up to set email alerts
|

Foreign aid and growth nexus: empirical evidence from South Asian countries

Abstract: PurposeThe purpose of this paper is to empirically examine the effectiveness of foreign aid in improving economic growth prospects in the South Asian region from 1996 to 2017.Design/methodology/approachA sample of eight South Asian countries for the period 1996–2017 is being considered for this study. This study uses various econometrics tools such as Pedroni and Johansen–Fisher panel cointegration test, panel fully modified ordinary least square and panel dynamic ordinary least square (PDOLS) to ascertain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 95 publications
0
13
1
Order By: Relevance
“…Their study also reveals that the combined effect of FA and institutions on economic growth is that it lessens the negative impact of FA on economic growth. Jena and Sethi (2020) revealed that FA has a significant long-run along with short-run association with investment, trade openness, financial deepening, economic growth, and price stability of the countries. In a detailed study Liu et al, (2020) revealed that financial deepening and Trade openness has a positive impact on attracting Foreign direct investment, which is another important element of the Economic growth of a country like FA.…”
Section: Brief Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Their study also reveals that the combined effect of FA and institutions on economic growth is that it lessens the negative impact of FA on economic growth. Jena and Sethi (2020) revealed that FA has a significant long-run along with short-run association with investment, trade openness, financial deepening, economic growth, and price stability of the countries. In a detailed study Liu et al, (2020) revealed that financial deepening and Trade openness has a positive impact on attracting Foreign direct investment, which is another important element of the Economic growth of a country like FA.…”
Section: Brief Review Of the Literaturementioning
confidence: 99%
“…FA, as well as Gross Capital Formation (GCF), Trade openness (TO), and Population Growth (PG) are the Independent variable. Following the study (Jena and Sethi, 2020;Kargbo, 2012;Orji et al, 2019), we are going to utilize the two-gap model for our study. The linear functional association between the Dependent variables and Independent variables stands:…”
Section: Theoretical Framework and Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies that explore financial development-education nexus are scarce most scholars that explore this relationship confirm the importance of education/HC in the development of the financial system and they noted that education is considered crucial in the way that the better-educated population, the more access to information, the more saving behavior and the less-risk averse the investors will be and they can make initiatives and start their business (Outreville, 1999; Kendall, 2007; Sharma, 2016; Ibrahim and Sare, 2018; Ibrahim, 2018; Sethi et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As financial institutions are among the basic factors that affect the country's economic development, financial development is considered a fundamental contributor to economic growth and so, financial development-economic growth nexus was first investigated by Schumpeter (1949) then Mckinnon (1973) and Shaw (1973). Then, several researchers suggest that financial development fosters gross domestic product, for instance, King andLevine (1993), De Gregorio andGuidotti (1995), Levine et al (2000), Christopoulos and Tsionas (2004), Chang and Caudill (2005), Saci et al (2009), Hosny (2012), Uddin et al (2013), Durusu-Ciftci et al (2017, Bist (2018), Guru and Yadav (2019), Aluko and Ibrahim (2020), Sethi et al (2020), Sahoo and Sethi (2020), Jena and Sethi (2020) and Yakubu et al (2021).…”
Section: Introductionmentioning
confidence: 99%